2014
DOI: 10.1086/674798
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress in Pacific Salmon (Oncorhynchus spp.) during Spawning Migration

Abstract: The energetic and physiological challenges of spawning migrations in semelparous Pacific salmon (Oncorhynchus spp.) have been well characterized. However, the accompanying costs associated with oxidative stress during this nonfeeding migration and the potential connection to senescence have not been explored. Oxidative stress is caused by an imbalance between free radical production and absorption, leading to irreparable cellular damage that accumulates over time and contributes to senescence. The objective of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 35 publications
3
25
0
2
Order By: Relevance
“…Our study showed that the liver might also be preferentially protected in populations making longer distance migrations, as antioxidant capacity was higher and oxidative stress lower in Stellako River compared to Chilko River. Wilson et al (2014) also assayed liver tissue but found no difference between pre-and post-migration for oxidative stress, however the spawning migration studied in this case was only~100 km and may not be long enough to observe the changes detected in the longer distance migrations. Once sockeye salmon fry complete yolk-sac absorption and emerge from the gravel redds, they must migrate to rearing areas (Quinn, 2005).…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Our study showed that the liver might also be preferentially protected in populations making longer distance migrations, as antioxidant capacity was higher and oxidative stress lower in Stellako River compared to Chilko River. Wilson et al (2014) also assayed liver tissue but found no difference between pre-and post-migration for oxidative stress, however the spawning migration studied in this case was only~100 km and may not be long enough to observe the changes detected in the longer distance migrations. Once sockeye salmon fry complete yolk-sac absorption and emerge from the gravel redds, they must migrate to rearing areas (Quinn, 2005).…”
Section: Discussionmentioning
confidence: 74%
“…Creek spawning grounds to compare oxidative stress pre-and postspawning migration (Wilson et al, 2014). Wilson et al (2014) found that brain tissue had both higher antioxidant capacity and lower DNA , and oxidative stress represented as a ratio of reduced glutathione to oxidized glutathione (GSH/GSSG) (C) for pre-fertilized eggs (PF), eggs at 24 h post-fertilization (24 HPF), eyed embryos (EYE), hatchlings (HA) and emergent fry (EMG, full yolk sac absorption) reared from female sockeye salmon captured at Harrison River (hashed bars), Chilko River (light gray bars), or Stellako River (dark gray bars) spawning sites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It adversely impacted fish welfare on several levels as growth [15] reproduction [16], and immunity [17].…”
Section: Introductionmentioning
confidence: 99%